1998
DOI: 10.1021/ac9712411
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enantiomer Bonding on a Chiral Stationary Phase by FT-Raman Spectrometry

Abstract: The bonding of serine, phenylalanine, and mandelic acid enantiomers on an N-3,5-dinitrobenzoyl-l-leucine chiral stationary phase (on zeolite A support) has been investigated by FT-Raman spectrometry. It was found that retention is due to hydrogen bonds and π-stacking interactions between the stationary phase and the analyte. The involvement of the two different amide groups (as donor and/or acceptor) in the complexation reaction can be followed based on spectral data. A correlation was found between the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…25 It is also known that longer aliphatic chains perturb hydrogen binding of analyte to the amide group involved in the primary recognition of enantiomers. 26,27 In conclusion, we have shown that efficient brush-type CSPs can be prepared by functionalization of the persub-stituted benzene derivative 1. In particular, those containing chiral, -basic (R)-NEA unit connected via a glycinetype spacer group can resolve a wide range of -acidic racemic compounds.…”
Section: Resultsmentioning
confidence: 75%
“…25 It is also known that longer aliphatic chains perturb hydrogen binding of analyte to the amide group involved in the primary recognition of enantiomers. 26,27 In conclusion, we have shown that efficient brush-type CSPs can be prepared by functionalization of the persub-stituted benzene derivative 1. In particular, those containing chiral, -basic (R)-NEA unit connected via a glycinetype spacer group can resolve a wide range of -acidic racemic compounds.…”
Section: Resultsmentioning
confidence: 75%
“…According to the literature data, the conclusion about the mechanism is mostly based on general deliberations, sometimes computer methods, 14 but rarely on using the NMR spectroscopy which requires a previous synthesis of CSPÕs analogues, 15 and recently on the using of IR and Raman spectroscopy of solid phases. 16,17 The latter is not completely pursuant to reality since, during the chromatography, chiral recognition evolves around the surface of solid carriers, not in the liquid phase. Therefore as the method, which could gather the most data about real interactions, we chose NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The chiral recognition mechanisms that separate chiral solutes having p-donor groups have been investigated by HPLC (Pirkle and Welch, 1984;Wainer and Alembik, 1986;, NMR spectrometry (Pirkle and Pochapsky, 1987), X-ray crystallography , Raman spectrometry (Horvóth et al, 1998) and computational studies (Lipkowitz et al, 1988;Topiol et al, 1988). The aim of these studies has been to clarify the interactions required for forming diastereomeric complexes that achieve complete enantiomeric separations.…”
Section: Introductionmentioning
confidence: 99%